SAP-Dependent and -Independent Regulation of Innate T Cell Development Involving SLAMF Receptors - De Calisto, Jaime; Wang, Ninghai; Wang, Guoxing; Yigit, Burcu; Engel, Pablo; Terhorst, Cox (Frontiers in Immunology, 2014)
Signaling lymphocytic activation molecule (SLAM)-associated protein (SAP) plays an essential role in the immune system mediating the function of several members of the SLAM family (SLAMF) of receptors, whose expression is essential for T, NK, and B cell responses. Additionally, the expression of SAP in double-positive (DP) thymocytes is mandatory for natural killer T (NKT) cells and, in mouse, for innate CD8+ T cell development. To date, only two members of the SLAMF of receptors, Slamf1 and Slamf6, have been shown to positively cooperate during NKT cell differentiation in mouse. However, it is less clear whether other members of this family may also participate in the development of these innate T cells. Here, we show that Slamf[1+6]-/- and Slamf[1+5+6]-/- B6 mice have an approximately 70% reduction of NKT cells compared to wild-type (WT) B6 mice. Unexpectedly, the proportion of innate CD8+ T cells slightly increased in the Slamf[1+5+6]-/-, but not in the Slamf[1+6]-/- strain, suggesting that Slamf5 may function as a negative regulator of innate CD8+ T cell development. Accordingly, Slamf5-/- B6 mice showed an exclusive expansion of innate CD8+ T cells, but not NKT cells. Interestingly, the SAP-independent Slamf7-/- strain showed an expansion of both splenic innate CD8+ T cells and thymic NKT cells. On the other hand, and similar to what was recently shown in Slamf3-/- BALB/c mice, the proportions of thymic PLZFhi NKT cells and innate CD8+ T cells significatively increased in the SAP-independent Slamf8-/- BALB/c strain. In summary, these results show that NKT and innate CD8+ T cell development can be regulated in a SAP-dependent and -independent fashion by SLAMF receptors, in which Slamf1, Slamf6, and Slamf8 affect development of NKT cells, and that Slamf5, Slamf7, and Slamf8 affect the development of innate CD8+ T cells.